Technologies for obtaining energy from micro-hydropower resources - Purece, Cristian; Vasile Pleşca; Lilica Corlan (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Currently the global demand for electricity and drinking water is constantly increasing. Given its many economic, social and environmental benefits, hydro energy will be an important contributor to the energy mix of the future. Isolated areas, heavily underdeveloped regions, disaster-affected areas have a common need of easy-to-use means to generate electricity. The most efficient way to meet these needs involves the use of various renewable energy resources available locally. One of the main sources of renewable energy is hydro energy, more specifically micro-hydro energy. However, hydropower projects involve various considerations at different levels of project implementation. To make the most of the available hydropower potential, new models of hydraulic turbines were developed. For a cost-effective and efficient hydropower project, the selection of the hydraulic turbine must be optimally studied. The objective of the present work is to carry out a review of the optimum selection mode of the hydraulic turbine that equips a micro hydropower plant (MHP).